Database of Parenthetic Biomedical Abbreviations - Turki, Houcemeddine; Hadj Taieb, Mohamed Ali; Ben Aouicha, Mohamed (My University, 2020)
This dataset includes the biomedical abbreviations stated between parentheses in the titles of the scholarly publications indexed by PubMed between 1947 and 2019. Each abbreviation is extracted thanks to the parenthetic level count algorithm and is assigned to the title, PMID and year of publication of each corresponding research paper. Then, every acronym is allocated its length and the number of upper and lower case letters it involves. Finally, the entities including one or no upper case letter, less than three characters, eight characters or more, or a high rate of non-alphanumeric characters are semi-automatically eliminated to ensure the consistency of the research database.
Keywords: Dataset; Parenthetic Abbreviations; Biomedical Abbreviations